2000
DOI: 10.1111/j.1365-2621.2000.tb13583.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Amines in Turkish Sausages (Sucuks)

Abstract: In this study, Turkish fermented sausage (sucuk) samples from different producers were examined with respect to their biogenic-amine contents, including histamine, tryptamine, and tyramine. The difference between amine levels of the samples produced through a starter-facilitated process and those produced without using a starter was investigated. Amines were extracted from the samples using perchloric acid and analyzed by HPLC in an ODS 2 column with a UV/VIS detector at 254 nm after derivatization with dansyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 15 publications
1
18
1
Order By: Relevance
“…Rabie et al (2014) found that day 28 histamine in beef sausage was on the level of 31.24 mg/kg. The other author found a histamine level from 6.72 to 768 mg/kg in diff erent kinds of fermented meat products (Ansorena et al, 2002;Rabie et al, 2010;Şenöz et al, 2000). A higher (p < 0.05) concentration of tyramine was noted for salted (S, W) fermented beef 369.5 mg/kg and 437.50 mg/kg respectively compared with cured (62.60 mg/kg).…”
Section: Resultsmentioning
confidence: 94%
“…Rabie et al (2014) found that day 28 histamine in beef sausage was on the level of 31.24 mg/kg. The other author found a histamine level from 6.72 to 768 mg/kg in diff erent kinds of fermented meat products (Ansorena et al, 2002;Rabie et al, 2010;Şenöz et al, 2000). A higher (p < 0.05) concentration of tyramine was noted for salted (S, W) fermented beef 369.5 mg/kg and 437.50 mg/kg respectively compared with cured (62.60 mg/kg).…”
Section: Resultsmentioning
confidence: 94%
“…The HPLC method used was modified method of Eerola, Hinkkanen, Lindfors, and Hirvi (1993) and Senoz, Isıklı, and Coksoyler (2000). This method involves dansyl derivatisation.…”
Section: Hplc Methodsmentioning
confidence: 99%
“…Histamine was also detected in Russian sausages, but usually not above 100 mg/kg (Hernandez-Jover et al, 1997). In the case of Turkish sausages, contents of 1,100 mg/kg of tyramine and 350 mg/kg of histamine were found in sucuks (Şenöz, Işıklı, & Çoksöyler, 2000), and 400 mg/kg of putrescine and 250 mg/kg of tyramine in soudjoucks (Ayhan, Kolsarici, & Özkan, 1999).…”
Section: Introductionmentioning
confidence: 94%